UTILIZATION OF STEM CELL RESEARCH IN MICROGRAVITY FOR INNOVATION IN CELLULAR THERAPY ON EARTH - Hendrizal; Dahlan; Gower (Stem Cell Research and Development Center, Universitas Airlangga, 2024)
Recent advancements in stem cell biology, coupled with developments in space exploration, have opened new avenues for regenerative medicine. Microgravity environments in space induce significant physiological changes in the human body, such as muscle atrophy, decreased bone density, and immune system impairments, mimicking accelerated aging and chronic disease progression. These conditions offer a unique opportunity to study stem cell behavior, proliferation, and differentiation, which occur at a faster pace in space compared to Earth. The three-dimensional (3D) microgravity environment provides a more accurate representation of the human body’s natural state than traditional two-dimensional culture systems, fostering enhanced stem cell development. Among the various stem cells studied in space, mesenchymal stem cells (MSCs) have shown promise for therapeutic applications, including the treatment of stroke, cancer, and neurodegenerative diseases. Research aboard the International Space Station (ISS) has demonstrated that MSCs maintain their properties, proliferate, and differentiate under microgravity conditions, offering potential for future therapies. Additionally, MSCs exhibit resistance to space radiation, protecting astronauts from its harmful effects by promoting tissue repair and releasing regenerative factors. This radiation resistance, coupled with cryopreservation techniques, enables MSCs to be used in long-duration space missions. The ongoing research on MSCs in space not only supports astronaut health but also holds the potential to revolutionize regenerative medicine on Earth. By understanding how microgravity influences stem cell behavior, scientists are uncovering critical insights into tissue repair and cell function, paving the way for innovative treatments for aging-related diseases and other medical conditions. These findings highlight the broader implications of space-based stem cell research for advancing human health both in space and on Earth.